Financial access, governance and the persistence of inequality in Africa: Mechanisms and policy instruments - Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2020)
The aim of this paper is to investigate policy instruments by which the persistence of inequality is affected through financial development channels in 48 African countries for the period 1996 - 2014. Financial dynamic channels of depth (money supply and liquid liabilities), efficiency (at banking and financial system levels), activity (from banking and financial system perspectives) and stability are used. Political ("voice and accountability" and political stability), economic (government effectiveness and regulation quality) and institutional (rule of law and corruption-control) governance policy instruments are also involved. The empirical evidence is based on the Generalised Method of Moments (GMM). The results show that financial depth and financial stability are the best channels of reducing inequality. Moreover, the relevance of these financial channels is significantly apparent when policy instruments are exclusively governance variables. The comparative relevance of governance dynamics in the persistence of inequality is discussed. The study responds to two recent policy and scholarly challenges, notably: the persistence of inequality in Africa and the relevance of governance in addressing income inequality by means of financial access.
Keywords: O16; O10; I30; C50; O55; 330; Finance; Governance; Inequality; Modelling; Africa